Phylogeny of Yersinia pestis Strains Belonging to 0.ANT Branch, Isolated in Tien-Shan and Pamir-Alay in XX–XXI Centuries - G. A. Eroshenko; A. K. Dzhaparova; E. G. Oglodin; Zh. V. Al’khova; L. M. Kukleva; A. A. Kuznetsov; Ya. M. Krasnov; S. T. Abdikarimov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2020)
Objective of the study was to conduct phylogenetic analysis of Yersinia pestis strains of the main subspecies, belonging to antique biovar, phylogenetic branch 0.ANT, isolated in XX – early XXI centuries in the foci of Tien-Shan and Pamir-Alay to identify the regularities of spatial-temporal circulation of plague agent in the territory of the foci. Materials and methods. We have carried out whole genome SNP-analysis of Y. pestis strains of antique biovar, isolated in natural foci of Kyrgyz Republic in 1928–2016. Phylogenetic investigation is based on 1646 identified core SNPs in 51 included in the analysis strains of different phylogenetic lines. Phylogenetic tree was constructed using Maximum Likelihood algorithm, PHYML software package, and HKY85 model. Results and discussion. All 29 studied Y. pestis strains isolated between 1928 and 2016 in the foci of Tien-Shan and Pamir-Alay fall under the phylogenetic branches 0.ANT3 and 0.ANT5 of antique biovar of the main subspecies. Strains of 0.ANT3 branch were collected predominantly in Aksay and Alay foci, while strains of 0. ANT5 – in Upper-Naryn and Sarydzhas foci of Tien-Shan. Strains of phylogenetic lines 0.ANT1 and 0.ANT2 were not found in the foci of Kyrgyz Republic. According to the results of whole genome SNP-analysis, Y. pestis strains isolated in the XXI century belong to phylogenetic branch 0.ANT5. This branch also comprises a strain obtained from a patient (lethal case) in Sarydzhas plague focus in 2013. Genetic homogeneity of the modern strains of 0.ANT5 branch and their wide dissemination testify to the extension of the areal of this population and activation of Tien-Shan foci, caused by climate warming. For the first time ever, genomes of Y. pestis 0.ANT5 branch, isolated in XXI century, including clinical strain dated 2013, have been sequenced. We have obtained the whole-genome sequence of Y. pestis strain, 0.ANT3 branch, which caused pneumonic plague outbreak in Tien-Shan in 1928.